2003
DOI: 10.1253/circj.67.511
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Imbalance as a Property of Symptomatic Brugada Syndrome

Abstract: The autonomic properties in 27 patients with the electrocardiographic morphology of Brugada syndrome were investigated using 24-h Holter monitoring: 10 patients had a history of ventricular fibrillation (VF; Br-VF group) and 17 did not (Br-N group); there were 26 healthy subjects enrolled in this study. All subjects underwent normal Holter data monitoring and power spectral analysis. Few extrasystoles were observed in either group, and the mean heart rate (HR), maximum HR, and total heart beats over 24 h were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 12 publications
(6 reference statements)
8
50
4
Order By: Relevance
“…Hence, it is unclear whether sodium channel dysfunction resulted in the sinus node impairment in the Brugada patients with VF induced by PES. Although the disease activity of BS is influenced by vagal nerve activity, 22,33 we did not evaluate the influence of the autonomic nervous system and the results of this study may have been influenced by autonomic nerve activity.…”
Section: Study Limitationmentioning
confidence: 90%
“…Hence, it is unclear whether sodium channel dysfunction resulted in the sinus node impairment in the Brugada patients with VF induced by PES. Although the disease activity of BS is influenced by vagal nerve activity, 22,33 we did not evaluate the influence of the autonomic nervous system and the results of this study may have been influenced by autonomic nerve activity.…”
Section: Study Limitationmentioning
confidence: 90%
“…For example, increased parasympathetic activity is suggested by a 24-hour Holter monitoring study, which showed that symptomatic BrS patients have lower mean heart rate than asymptomatic patients. 17 Moreover, right precordial STsegment elevation in BrS patients increases after intracoronary injection of the parasympathetic neurotransmitter acetylcholine. 18 Decreased sympathetic activity is suggested by clinical studies, which investigated the myocardial presynaptic and postsynaptic sympathetic function in BrS patients.…”
Section: Heart Ratementioning
confidence: 99%
“…20 Modulation abnormalities of the autonomic system may directly affect the ECG properties and increase vulnerability to fatal arrhythmias. 21,22 Several reports [23][24][25][26] showed, for BS patients, that ST-segment elevations on 12-lead ECGs have diurnal and daily variations; therefore, it is considered that the occurrence of events may also have circadian and daily variations. Matsuo et al 26 analyzed the circadian pattern of 30 ventricular fibrillation episodes in 12 BS patients who underwent an implantable cardioverter-defibrillator treatment and reported that ventricular fibrillation occurred more frequently at night (93%) than during the day (7%).…”
Section: Discussionmentioning
confidence: 99%